1991
DOI: 10.1002/jab.770020409
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast shape conformation to surface micromorphology

Abstract: Fibroblasts in culture and in vitro have been shown to interact with certain surface morphological phenomena. It was the aim of the present study to determine cellular morphological interactions with surface grooves of subcellular dimensions. The silicon oxide layer of a wafer was photoetched, which resulted in a regular micromorphology with linear rectangular shaped microbars and microgrooves 1, 1.5, and 2 pm in diameter and distance from each other. Human fibroblasts were seeded on the sterile specimen and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Attached fibroblasts exhibited normal characteristics with spreading and process formation indicative of viable cell attachment and growth when compared with the control substrate. Meyle et al 28 studied the effect of fibroblast shape conformation to microgrooves on silicon wafer and showed that once the cell has received sufficient stimuli to indicate that the surface is favorable for cell attachment, the cell can detect the topography of the surface by forming focal contacts to the substrate. The cell would then increase its contact area by an active flattening and flowing motion into surface contours by use of numerous filopodia and lamellipodia, which may then result in alignment of the cells with any ridges on the substrate.…”
Section: Discussionmentioning
confidence: 98%
“…Attached fibroblasts exhibited normal characteristics with spreading and process formation indicative of viable cell attachment and growth when compared with the control substrate. Meyle et al 28 studied the effect of fibroblast shape conformation to microgrooves on silicon wafer and showed that once the cell has received sufficient stimuli to indicate that the surface is favorable for cell attachment, the cell can detect the topography of the surface by forming focal contacts to the substrate. The cell would then increase its contact area by an active flattening and flowing motion into surface contours by use of numerous filopodia and lamellipodia, which may then result in alignment of the cells with any ridges on the substrate.…”
Section: Discussionmentioning
confidence: 98%
“…Also it has been demonstrated that glow discharge treatment results in a hydrophilic silicone surface with similar properties and cellular reactions to those already observed on silicon oxide and araldite [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…This line pattern was developed in a wet etching process which resulted in a regular surface microstructure with a groove depth of 1 lam arid a groove width of 4 gm separated by rectangular ridges of 1 gm. For a more detailed description of the production of the wafer surface see [6].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations